The UNIX operating system - Christian, Kaare (Wiley profesional computing, 1994)
Written in the same clear, accessible style as the bestselling Second Edition, this new edition of Kaare Christian's the UNIX Operating System contains all the information you need to use the UNIX System V operating system in business, science, and industrial applications. With more than 50% new and expanded material that reflects the dramatic changes to UNIX since 1989, the text guides you through every aspect of UNIX - from basic commands to shell programming to advanced functions like systems administration. In addition to providing you with useful tables that summarize the key command line options for most important commands, the Third Edition also includes new chapters on security, windowing systems, networking, and systems administration. Whether you're a novice or someone who manages and utilizes information on a UNIX system every day of the week, The UNIX Operating System, Third Edition is an essential source of up-to-date information and practical tools for discovering one of the world's most popular operating systems